2022
DOI: 10.1007/s00430-022-00740-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood and saliva SARS-CoV-2 antibody levels in self-collected dried spot samples

Abstract: We examined the usefulness of dried spot blood and saliva samples in SARS-CoV-2 antibody analyses. We analyzed 1231 self-collected dried spot blood and saliva samples from healthcare workers. Participants filled in a questionnaire on their COVID-19 exposures, infections, and vaccinations. Anti-SARS-CoV-2 IgG, IgA, and IgM levels were determined from both samples using the GSP/DELFIA method. The level of exposure was the strongest determinant of all blood antibody classes and saliva IgG, increasing as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[28][29][30] To overcome the challenge associated with low total IgG concentrations in saliva compared to blood some have resorted to concentrating saliva, either with or without additional accounting for salivary total IgG, which resulted in increased assay sensitivity but reduced specificity. 31 Despite the lower assay performance most groups found that blood SARS-CoV-2 IgG levels correlate well with salivary IgG levels 32 , however, such findings are often based on very small sample sizes. 31,33,34 Studies with larger sample sizes typically report less robust correlations between saliva and blood antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] To overcome the challenge associated with low total IgG concentrations in saliva compared to blood some have resorted to concentrating saliva, either with or without additional accounting for salivary total IgG, which resulted in increased assay sensitivity but reduced specificity. 31 Despite the lower assay performance most groups found that blood SARS-CoV-2 IgG levels correlate well with salivary IgG levels 32 , however, such findings are often based on very small sample sizes. 31,33,34 Studies with larger sample sizes typically report less robust correlations between saliva and blood antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic the use of air turbine handpiece and ultrasonic scaler were prohibited in most countries as dental professionals were thought to be more prone to SARS-CoV-2 infection compared to other healthcare occupational groups [ 8 , 9 , 10 ]. However, contrary findings were published as the pandemic evolved and dental professionals had lower SARS-CoV-2 antibody levels compared to other healthcare professionals [ 11 ] and studies indicating dental procedures do not produce much aerosol particles size smaller than 10 μm if high-volume suction or external high-volume extraction device was properly used [ 2 , 3 , 4 , 5 ]. Additionally, personal protective equipment (PPE) in dentistry was improved when FFP-masks, face shields and hair covers were routinely recommended to use in the beginning of pandemic, and studies have been published indicating low numbers of work-related exposures in dental staff [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%